Antecedents of Turnover Intention with Mediation Role of Overall Satisfaction: Thailand Rubber Industry - Jermsittiparsert, Kittisak; Namdej, Puttisat; Siriattakul, Parinya (International Journal of Psychosocial Rehabilitation, 2019)
The study is carried out to exercise the workforce diversity, flexible work timings, and CSR activities as the determinants of overall satisfaction, which ultimately leads to low turnover intentions. In addition to that, the trust is examined as a moderator in the relationship between workforce diversity and overall satisfaction. Lastly, satisfaction is examined as a mediator. The current study has employed SEM-PLS to achieve the research objectives. The study has extended the literature on the turnover intention by proving the overall employee satisfaction as a mediator between diversity, flexible timings, CSR activities and turnover intention relationship. 124 employees in the Thai rubber industry are the final sample of the current study. The findings of the study have provided support to the proposed hypothesis. The findings of the study will provide support to the policymakers, researchers, and practitioners in understanding the fact that all of the stakeholders are impacted in a positive manner by these activities of the organization. according to CSR, it is important for organizations to follow the legislation, take the initiative voluntary so the wellbeing of employees and their families can be improved and for the society and community as well